HUBUNGAN SELF CARE DENGAN KUALITAS HIDUP PASIEN GAGAL JANTUNG - Samfriati Sinurat; Mardiati Barus; Bunga Angelia Siregar (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Heart failure is a cardiovascular disease that continues to increase in incidence and prevalence and the number one cause of death worldwide. Heart failure patients experience a decrease in the ability of the heart muscle to pump blood and meet the oxygen needs of the body. This results in a low quality of life for heart failure patients, so self care is needed to improve the quality of life for heart failure patients. Self care is an activity to maintain health and well-being. This study aims to identify the relationship between self-care and the quality of life of patients heart failure at RSUP Haji Adam Malik Medan.This type of quantitative research with cross sectional method. The population of this research is heart failure patients who experience outpatient services at the RSUP Haji Adam Malikin Medan in 2021 and taking sample of 84 respondents using purposive sampling technique. Data collection using a questionnaire.The results showed that the majority of selfcare for heart failure patients at RSUP Haji Adam Malik Medan in 2021 was good (76.2%) and the majority of the quality of life was high (88.1%). The results of the fisher exact statistical test obtained p-value of 0.001 indicating a significant relationship between Self Care and Quality of Life for Heart Failure Patients at RSUP Haji Adam Malik Hospital Medan in 2021. It’s hoped that respondents will further improve selfcare and quality of life in themselves so that they can enjoy life together with family and people around